Swimming in Deep Water: Zebrafish Modeling of Complicated Forms of Hereditary Spastic Paraplegia and Spastic Ataxia - Naef, Valentina; Mero, Serena; Fichi, Gianluca; D'Amore, Angelica; Ogi, Asahi; Gemignani, Federica; Santorelli, Filippo M.; Marchese, Maria (Frontiers in Neuroscience, 2019)
Hereditary spastic paraplegia (HSP) and hereditary ataxia (HA) are two groups of disorders characterized, respectively, by progressive dysfunction or degeneration of the pyramidal tracts (HSP) and of the Purkinje cells and spinocerebellar tracts (HA). Although HSP and HA are generally shown to have distinct clinical-genetic profiles, in several cases the clinical presentation, the causative genes, and the cellular pathways and mechanisms involved overlap between the two forms. Genetic analyses in humans in combination with in vitro and in vivo studies using model systems have greatly expanded our knowledge of spinocerebellar degenerative disorders. In this review, we focus on the zebrafish (Danio rerio), a vertebrate model widely used in biomedical research since its overall nervous system organization is similar to that of humans. A critical analysis of the literature suggests that zebrafish could serve as a powerful experimental tool for molecular and genetic dissection of both HA and HSP. The zebrafish, found to be very useful for demonstrating the causal relationship between defect and mutation, also offers a useful platform to exploit for the development of therapies.